Penggunaan Limbah Nikel Sebagai Material Subtitusi Agregat Kasar Pada Beton K.250 - Muhsar, Muhammad; Kadir, Abdul; Sulaiman, Sulaiman (Sultra Civil Engineering Journal (SCiEJ), 2021)
The purpose of this study was to Analyze the characteristics of the aggregates used in concrete mixtures and analyze how much increase in compressive strength of concrete with a variation of nickel slag substitution 0%, 5%, 15%, 25% compared with normal concrete. The characteristics of the material examined are water content, sludge content, specific gravity and absorption, volume weight, abrasion with los angeles machines, and filter analysis. While the large increase in compressive strength of concrete can be tested at the age of 7 days, 14 days, 28 days and 35 days. From the results of the analysis of the characteristics of nickel slag waste in concrete mixes meet the test standards in concrete mixtures, with a moisture content of 0.86%, sludge content of 0.44%, specific gravity of 2.94 gr / cm3, volume weight of 1.76 gr / cm3, abrasion 36.07%. And a large increase in compressive strength of concrete with a variation of nickel slag substitution of 0%, 5%, 15%, 25% compared to normal concrete is increasing. The highest percentage increase in concrete compressive strength is found in concrete compressive strength between a variation of 15% with a variation of 25% at 14 days concrete age, with a percentage increase in value of 13.13%.